Pengaruh Media Video Tutorial Pembuatan Snack Bouquet terhadap Kemampuan Vokasional pada Siswa dengan Disabilitas Rungu Kelas X - Yusuf, Aulia Yasmin; Nurhadiyati, Arifah; Sukmawati, Bhennita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to investigate the impact of using a video tutorial on creating snack bouquets on the vocational skills of 10th-grade deaf students at Jember State Special Needs School. The method used by the researchers in this study was a quantitative experiment, a pre-experimental study with a one-group pretest-posttest design. The study population consisted of four students. Data were processed using nonparametric statistical methods, using the sign-and-sign test. Based on the results, it can be concluded that the video tutorial on making snack bouquets has a positive effect on improving the vocational skills of 10th-grade deaf students at Jember State Special Needs School. This media offers a visual approach tailored to students' needs, facilitating an understanding of instructions without relying on verbal communication, and encourages students to learn independently. This research demonstrates the importance of implementing adaptive learning media, particularly in supporting inclusive education for students with special needs. Keywords: Video Tutorial Media, Vocational Skills, Students with Deafness